Pengaruh Gaya Hidup Hedonisme Dan Promo Tanggal Kembar Terhadap Impulse Buying : Studi Kasus Pengguna Shopee Di Tangerang Selatan - Nurul Eka Putri; Ambardi Ambardi (Pusat Riset dan Inovasi Nasional, 2023)
This study was structured to determine the effect of the Hedonism Lifestyle and Twin Date Promos on Impulse Buying for Shopee users in South Tangerang. The method used in this study is a quantitative method with the type of associative descriptive research. This study uses primary data obtained by making questionnaires and then distributed to respondents who match the research criteria, the data is then analyzed using the classical assumption test and hypothesis testing. The statistical method in this study uses multiple linear regression analysis with the help of SPSS version 24. The results of this study indicate that there is a significant influence between the Hedonism Lifestyle and Twin Date Promo on Impulse Buying for Shopee users in South Tangerang.